Beyond stakeholder engagement: the challenges of stakeholder participation in corporate governance. (2nd November 2004) - Low, Christopher; Cowton, Christopher
The UK Government is presently conducting a consultation process focused on the introduction of a new legal form of company, that of the Community Interest Company (CIC). Organisations choosing this form of incorporation would be subject to a legal requirement to involve their stakeholders in the governance of the company. This development is just the latest example of an increased interest generally in making companies more responsive to their stakeholders. The statutory duty placed on companies taking the CIC form raises the possibility of further legislation being introduced to compel all companies to involve their stakeholders more formally in their governance. This paper examines the participation model of stakeholder involvement proposed in the CIC legislation. This model is already widely employed in the not-for-profit company sector. A comparison is made with the engagement model of stakeholder management which is the most popular form found within the corporate sector. Conclusions are subsequently drawn about the appropriateness of a participation model for corporations in the for-profit sector by examining the challenges that emerge from giving stakeholders such a prominent role in the strategic management of the organisation.